ANTIPROLIFERATIVE ACTIVITY OF ELEPHANTOPUS SCABER MEDIATED SILVER NANOPARTICLES AGAINST MCF-7, A-549, SCC-40, AND COLO-205 HUMAN CANCER CELL LINES - S SHINDE, ASHWINI; MENDHULKAR, VIJAY D (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: To unearth the applications of nanotechnology in medicine has become imperative with all the advancements in the technique. In the current study, we have attempted to exploit the anticancer ability of the green synthesized silver nanoparticles (AgNPs). Methods: The AgNPs were synthesized using 60% methanol (H-MeOH) Elephantopus scaber leaf extract, characterized, and discussed priorly. The effect of AgNPs was studied on the human breast (MCF-7), lung (A-549), oral (SCC-40), and colon (COLO-205) cancer cell lines through sulforhodamine B assay. We also carried out the synergistic activity with standard drug adriamycin (ADR). Results: According to the results obtained, AgNPs showed good antiproliferative activity with GI50 <10 μg/ml on MCF-7, A-549, and SCC-40 cell lines when compared with the standard drug ADR. However, for COLO-205 cell line, the impact was 17.4 μg/ml and thus the treatment was less effective. Conclusion: The synergistic effect of AgNPs+ADR was even better for all the four cell lines than that of the AgNPs alone.